PENGARUH FASILITAS PELAYANAN, KEMAMPUAN KERJA, DAN RESPONSIVENESS TERHADAP KEPUASAN WAJIB PAJAK (Studi Kasus Pada Wajib Pajak yang Terdaftar di Kantor Pelayanan Pajak Pratama Wates) - Andri Waskita Aji; Teguh Erawati; Meidella Kartika Murti (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
This study aims to determine the effect of service facilities, work ability, and responsiveness on taxpayer satisfaction. This type of research is an associative type of research and data collection uses primary data using a questionnaire via google form. In this study samples were taken namely taxpayers who were registered at the Wates Pratama Tax Office. The sampling technique used purposive sampling technique with the criteria of taxpayers registered at KPP Pratama Wates and taxpayers who had visited KPP Pratama Wates. The number of processed data is 100 respondents. This study uses data analysis, namely multiple regression analysis which is processed using the SPSS version 20 program. The results show that service facilities have a positive effect on taxpayer satisfaction. Work ability has no effect on taxpayer satisfaction. Responsiveness has a positive effect on taxpayer satisfaction. Service facilities, work ability, and responsiveness simultaneously have a positive effect on taxpayer satisfaction